Economic Burden of Multidrug-Resistant Gram-Negative Infections in a Developing Country - Aysegul Ulu Kılıç; Gamze Kalin Unuvar; Fatma Cevahir; Emine Alp (Erciyes Medical Journal, 2019)
Objective: Antibiotic-resistant infections represent a significant global public health threat due to their rising prevalence. The aim of this study is to identify risk factors for acquisition of multidrug-resistant gram negatives (MDR-GNs) in the first intensive care unit (ICU) infection episode of patients and also to calculate the economic burden of infection with MDR-GNs that the ICU patient faced. Materials and Methods: This is a prospective observational study conducted over 1 year. The first ICU infection episode of the patients was included into this study. A case was defined as a patient who had an MDR-GN in his or her first episode of an ICU infection, and control was defined as a patient who had a non-MDR-GN in his or her first episode of an ICU infection. Results: A total of 100 patients were included into the study. Sixty-two patients had the MDR-GN, and 38 patients had a non-MDR pathogen. Independent risk factors associated with the MDR-GN infection were the APACHE II score (OR=1.08, p=0.012), transfer from another hospital (OR=9.3, p=0.04), antibiotic use before ICU infection (OR=7.7, p=0.04), and arterial catheter (OR=2.8, p=0.03). The median antibiotic cost was significantly higher for patients in the case group [$663.50 (27–3,752) and $256.00 (0–2,716), respectively] (p<0.01). Also, a total hospital cost for patients was significantly higher in the case group ($8,895 [2,621–23,883] and $6,551 [1,441–20,425], respectively) (p<0.05). Conclusion: Patients with a high APACHE II score transferred from another hospital and who use an antibiotic before the ICU infection and arterial catheter are at a greater risk of MDR-GN infections. Also, the infections pose a significant burden on health care facilities due to more prolonged and costly treatments.